Adaptation of pain scales for parent observation: are pain scales and symptoms useful in detecting pain of young children with the suspicion of acute otitis media? - Johanna M. Uitti; Sanna Salanterä; Miia K. Laine; Paula A. Tähtinen; Aino Ruohola (BMC, 2018)
Abstract Background The assessment of ear pain is challenging in young, mostly preverbal children. Our aim was to investigate whether pain scales are useful tools for parents to detect pain in their young children with the suspicion of acute otitis media (AOM), and to assess associations between 16 symptoms and the severity of pain. Methods This cross-sectional study included 426 children (6-35 months) with symptoms suggestive of AOM. We surveyed symptoms and pain via parental interview. As part of the interview, parents assessed their child's pain by using two pain scales: The Faces Pain Scale-Revised (FPS-R) and the Face, Legs, Activity, Cry, Consolability (FLACC) Scale. The outcome of interest was moderate/severe pain. We used the χ2 test or Fisher's test as applicable to compare the severity of pain between three parental pain assessment methods (the parental interview, the FPS-R and the FLACC Scale). We also used multivariable logistic regression models to study the association between the severity of pain and AOM and to study the association between symptoms and the severity of pain. Results In children with AOM (n = 201), pain was assessed by parents as moderate/severe in 65% via interview; 90% with the FPS-R; and 91% with the FLACC Scale (P < 0.001). In children without AOM (n = 225), the percentages were 56, 83 and 88%, respectively (P < 0.001). Between children with and without AOM, the occurrence of moderate/severe pain did not differ with any of the pain evaluation methods. Of symptoms, ear pain reported by child and restless sleep were significantly associated with moderate/severe pain, regardless of the pain evaluation method. Conclusions It seems that nearly all the children with respiratory tract infection, either with or without AOM, might suffer from moderate/severe pain. Without pain scales, parents may underestimate their child's pain. Of symptoms, ear pain reported by child and restless sleep might indicate pain in children with respiratory tract infection. We suggest that the adaptation of pain scales for parent observation is a possibility in children with respiratory tract infection which, however, requires further studies. Trial registration www.clinicaltrials.gov, identifier NCT00299455. Date of registration: March 3, 2006.